Eficiência do monitoramento da balneabilidade da costa marítima de Fortaleza: análise do período de 2019 a 2021 - Rocha, Yohanna Carvalho Rodrigues (2023)
The bathability of the sea coast of coastal cities is of great importance to society in various dimensions such as economic, social and environmental. However, there are many challenges to balance the different interests in this very important environmental area, which has natural riches often exploited by the economic sector linked to tourism, but which can also suffer from the consequences of accelerated and disorganized urbanization of large cities. The municipality of Fortaleza in Ceará is recognized for its beaches with natural beauty that attract a large number of tourists annually. The government of the state of Ceará, through the State Superintendence of the Environment of Ceará (SEMACE), develops the Beach Bathing Monitoring Program whose main objective is to monitor the quality of water on beaches throughout the state for primary use; this program has a wider range of monitoring points along the edge of Fortaleza. The present study aimed to analyze the efficiency of monitoring the seafront of Fortaleza, and used the Data Envelopment Analysis (DEA) technique as a quantitative analysis instrument and complemented with the qualitative analysis of the results obtained after treatment of data on monitoring bathing conditions on the sea coast of Fortaleza. DEA uses decision units (DMU) analyzing their performance in the use of their inputs (inputs) to produce the outputs (outputs). The inputs of the decision units were: (i) Number of collections carried out in the period; and (ii) Density of Bathing Monitoring on Fortaleza's Beaches in the period. The outputs of the decision units were: (i) Bathing - Number of bathing results in the period (Fortaleza); and (ii) Number of bathing bulletins issued in the period. Five different analysis scenarios were used with the available input and output variables on bathing conditions in Fortaleza, taking as DMUs the three years of management of the Bathing Program (2019 to 2021). The chosen period is justified because it is a strategic moment for the bathing monitoring program, with significant changes in its internal and external environment, such as the COVID19 pandemic. The results showed that the lowest efficiency result in all scenarios was 82.30% (most efficiencies were 100%) and that, therefore, the monitoring of bathing conditions on the coast of Fortaleza can be considered efficient in view of the sample chosen for this study. analysis, but that there is room for improvements to be implemented, such as corrective or preventive interventions, based on analyzes of a high number of results of unsuitable beaches for bathing.